The Impact of Zakat, Infak, and Sedekah Distribution, Gross Regional Domestic Product, Open Unemployment Rate, and Gini Index on Poverty in 34 Provinces of Indonesia from 2015 to 2025 - Rifqy Bayu Laksana; Laila Masruro Pimada (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Poverty is a persistent multidimensional development issue in Indonesia. This study aims to analyze the impact of the distribution of Zakat, Infak, and Sedekah (ZIS), Gross Regional Domestic Product (GRDP), Open Unemployment Rate (OUR), and Gini Index on poverty in 34 provinces of Indonesia during the period of 2015–2025. Using secondary panel data (N = 338), all independent variables were transformed with a one-period lag (t-1) to capture the delayed effects of policies and to reduce (but not eliminate) potential endogeneity. Based on the testing results, the Fixed Effect Model (FEM) with a Robust Variance Covariance Estimator (Robust VCE) approach was chosen to address violations of classical assumptions. The findings indicate that the previous period's ZIS has a positive and significant effect on the number of poor people (coefficient 0.238; p = 0.000), while GRDP, OUR, and the Gini Index do not have a significant effect. These results should not be interpreted as evidence that ZIS causes poverty, but rather as an association reflecting the targeting effect (funds following the poverty map), the dominance of consumptive distribution patterns, and the small scale of ZIS collection compared to the magnitude of the problem. With these characteristics, and based on supporting data and previous research, ZIS is interpreted as a palliative instrument that alleviates the depth and severity of poverty but has not yet succeeded in lifting beneficiaries above the poverty line, resulting in no decrease in the number of poor people.